(untitled) (Bangladesh Journal of Medical Science, 2022)
Background: The infectious diseases of viral etiology with airborne transmission generally dominate in the structure of infectious incidence. Objective: To determine incidence of viral infections with airborne transmission in the north-eastern region of Ukraine, to research the impact of social and natural factors on the intensity of epidemic process. Methods: In order to determine the current epidemiological peculiarities of infections with airborne transmission in the north-eastern region of Ukraine, a retrospective and operative analysis of the incidence, reports of vaccination of decreed child population in 2009‒2019, demographic and natural indicators. Results: Trends in the incidence of influenza were characterized by chaotic nature and disorder, acute respiratory viral infections ‒ high intensity and monotony. Significant correlations were established between the incidence of influenza and number and density of the population, the incidence of acute respiratory viral infections and the coefficient of migration population movement. Direct strong correlations were found between social factors and trends in the incidence of rubella and mumps. Coronavirus infection COVID–19 has become the problem for health care facilities in Sumy oblast. Conclusion: Quantitative and qualitative characteristics of the epidemic process of infections of viral etiology with airborne transmission have changed, which requires new approaches to organization of the system of epidemiological surveillance. Bangladesh Journal of Medical Science Vol. 21 No. 03 July’22 Page: 610-619